Micro-Raman Spectroscopy : Theory and Application - Mayerhöfer, Thomas; Popp, Jürgen (De Gruyter, 2020)
Micro-Raman Spectroscopy introduces readers to the theory and application of Raman microscopy. Raman microscopy is used to study the chemical signature of samples with little preperation in a non-destructive manner. An easy to use technique with ever increasing technological advances, Micro-Raman has significant application for researchers in the fields of materials science, medicine, pharmaceuticals, and chemistry.- Resumé vydavatel
Keywords: Ramanova spektroskopie; mikroskopie; Raman spectroscopy; elektronické knihy; sborníky; electronic books; papers of several authors